2, 6-Diaminopyridine decorated reduced graphene oxide as integrated electrode with excellent electrochemical properties for aqueous supercapacitors. (1st February 2022) - Zhang, Weiyang; Li, Yanchun; Kang, Hongwei; Yang, Baocheng; Li, Zhikun; Liu, Huili
Highlights: A novel 2, 6-diaminopyridine decorated reduced graphene oxide (RGO) composites (RGO/DAPs) with hierarchical porous structure are successfully synthesized via a simple one-step solvothermal method. The RGO/DAPs exhibits high specific capacitance, enhanced rate capability, good conductivity in aqueous electrolyte. The RGO/DAP-1.5//AC device delivers a high energy density of 14.55 W h kg−1 (350 W kg−1) and a super-long cycling stability with a satisfactory capacitance retention of 85.56% after 20 000 cycles. Abstract: Active organic small molecules are potential energy storage materials because of their renewable natural abundance, light weight and excellent electrochemical reversibility. However, the poor electrical conductivity and cycling stability force it to form composite materials to improve these performance. In this paper, 2, 6-diaminopyridine (DAP) decorated reduced graphene oxide (RGO) composites were successfully synthesized by a simple one-step solvothermal method. Benefiting from the pseudocapacitance provided by organic molecules DAP and the excellent conductivity of RGO, as well as the enhanced hydrophilicity and structural stability obtained by the synergistic effect of the two electrode materials, the synthesized RGO/DAP nanocomposites electrodes with hierarchical porous structure have been demonstrated to have excellent electrochemical properties in sustainable aqueous supercapacitors, such as higher specific capacitance, enhanced rate capability, good conductivity and excellent cycling stability. The assembled RGO/DAP-1.5//AC asymmetric supercapacitor device delivers a maximum energy density of 14.55 W h kg −1 at a power density of 350 W kg −1, and a super-long cycling stability with a satisfactory capacitance retention of 85.56% after 20 000 cycles. This result reveals a novel graphene-based composite electrode containing amino active organic molecules with great potential for application of aqueous energy storage devices. Graphical abstract: Capacitance retention at a high scan rate of 60 mV s −1 over 20 000 cycles. Insert shows the schematic illustration for the synthesis process of RGO/DAP nanocomposites. Image, graphical abstract